Surface polysaccharide mutants reveal that absence of O antigen reduces biofilm formation of Actinobacillus pleuropneumoniae. - Hathroubi,S; Hancock,MA; Bossé,JT; Langford,PR; Tremblay,YD; Labrie,J; Jacques,M (Infection and Immunity, 2015)
Actinobacillus pleuropneumoniae is a Gram-negative bacterium belonging to the Pasteurellaceae family and the causative agent of porcine pleuropneumonia, a highly contagious lung disease causing important economic losses. Surface polysaccharides including lipopolysaccharides (LPS) and capsular polysaccharides (CPS) are implicated in the adhesion and virulence of A. pleuropneumoniae, but their role in biofilm formation is still unclear. In this study, we investigated the requirement of these surface polysaccharides in biofilm formation by A. pleuropneumoniae serotype 1. Well characterized mutants were used: an O-antigen LPS mutant, a truncated core-LPS mutant with an intact O-antigen, a capsule mutant and a poly-N-acetylglucosamine (PGA) mutant. We compared the amount of biofilm produced by the parental strain and the isogenic mutants using static and dynamic systems. Compared to the parental or other strains, the biofilm of the O-antigen and the PGA mutants was dramatically reduced and it had less cell-associated PGA. Real-time PCR analyses revealed a significant reduction in the level of pgaA, cpxR and cpxA mRNA in the biofilm cells of the O-antigen mutant compared to the parental strain. Specific binding between PGA and LPS was consistently detected by surface plasmon resonance but the lack of O-antigen did not abolish these interactions. In conclusion, the absence of the O-antigen reduces the ability of A. pleuropneumoniae to form a biofilm and this is associated with a reduction in the expression and the production of PGA.